The rise of megacities : challenges, opportunities and unique characteristics - Kleer, Jerzy; Anna Nawrot, Katarzyna (London ; Hackensack : World Scientific Publishing Europe Ltd, 2018)
Megacities of over 10 million inhabitants are unique entities in their own right, both challenging and supporting the policies, governance and cohesion of states.
The complexity of and challenges in the emergence of megacities -- The rise of megacities : an empirical overview of the demographic changes in the world economy and an introduction to an integral theory of megacities / Jerzy Kleer and Katarzyna A. Nawrot -- Megacities : devastation of the public sphere / Jerzy Kleer -- From metropolis to megacity / Piotr Korcelli and Ewa Korcelli-Olejniczak -- Governance of megacities : selected aspects of international experience / Tadeusz Markowski -- Development patterns of megacities and their future / Zygmunt Ziobrowski -- Threats and challenges posed by the rise of megacities / Konrad Prandecki, Wojciech Kazanecki and Sylwia Smietanko -- Megacities and threats to human health / Agata Penconek -- The impact of megacities on human nature / Maria Szyszkowska -- Opportunities in the development of megacities : regional, national and multidisciplinary perspectives -- Rural-urban migration, urbanization and megacities in China / Feng Wengmeng -- Megacities in India : where are the opportunities? / Gaurang Rami And Yogesh N. Vansiya -- African megacities as emerging innovation ecosystems / Katarzyna A. Nawrot, Calestous Juma and James Donald -- A smart future for energy in megacities / Jessen Page -- What future lies ahead for megacities in Europe? / Jerzy Kleer and Katarzyna A. Nawrot -- Case studies of selected megacities -- Tokyo and Delhi : a comparative analysis of Asian megacities / Katarzyna A. Nawrot -- Shanghai : the first megalopolis on the globe? / Bogdan Góralczyk -- Mexico City : an antithesis of sustainable development? / Urszula Zulawska and Elzbieta Zulawska-Sobczyk -- Dhaka : the perils and promises of an Asian megacity / Adnan Morshed -- Lagos : directions of development of Nigerian metropolis in the first decades of the 21st century / Malwina Bakalarska -- New York : a city of progress / Bohdan Szklarski and Piotr Szyja -- Epilogue -- In lieu of a conclusion: megacities : boon or bane? / Jerzy Kleer and Katarzyna A. Nawrot.
Includes bibliographical references and index.
AAL
Complimentary Book
Keywords: Urbanization; Cities and towns